Fermentasi Pakan Maggot (Hermetia illucens) untuk Sintasan dan Pertumbuhan Ikan Nila (Oreochromis niloticus). - Alifia, Frida; Nurwahidah, Nurwahidah; Heriansah, Heriansah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
This study aims to examine the effect of fermented maggot feeding on the survival and growth of tilapia (Oreochromis niloticus) as an effort to increase feed efficiency in fish farming. Maggots are known as an alternative feed source rich in protein, but the fermentation process is needed to increase the digestibility and availability of nutrients. This study was conducted for six weeks at the Moncongloe Aquaculture Institute using an experimental trial method with a Completely Randomized Design (CRD) consisting of four treatments, namely A (maggots without fermentation as a control), B (maggots fermented with SLS), C (maggots fermented with EM4), and D (maggots fermented with Yakult), with each treatment being repeated three times. The main parameters measured included survival and absolute weight growth of tilapia. Based on the results of the study, the highest survival data was obtained in treatment B with a value of 86.7%, followed by treatments C and D which were each 83.3%, and treatment A (control) of 73.3%. Meanwhile, the absolute weight growth parameter showed the highest value in treatment B at 5.92 g, followed by treatment C at 5.79 g, treatment D at 5.58 g, and treatment A at 5.29 g. The results of the analysis of variance (ANOVA) revealed that the provision of fermented maggot feed did not have a significant effect on the survival of tilapia, but had a significant effect on its absolute weight growth. The treatment of maggot fermented with SLS (treatment B) showed superior results compared to other treatments, indicating that certain types of fermentation can increase the effectiveness of feed in supporting the growth of tilapia. Thus, this study provides scientific evidence that maggot fermentation, especially using SLS, is a potential method to improve the quality of fish feed, so that it can be applied as an innovation in the development of more efficient and sustainable fish farming